Study on toxic chemicals in Kuantan (Pahang) River during pre and post monsoon season - Md. Mokhlesur, Rahman; Awang, Mohamed; Khan Chowdhury, Ahmed Jalal; S., Aisha; Yunus, Kamaruzzaman (2011)
A study on water quality based on physico-chemical parameters and toxic heavy metals were carried out from October 2010 and January 2011 at Kuantan River, Pahang, Malaysia. Three stations were expected to be polluted was chosen to be studied in this project. The three chosen stations were area near to fish landing jetty, adjacent to the Hospital Kuantan and River estuary, in which in-situ measurements, samples were collected during low tides time zone and samplings for laboratory analysis were carried out. The results of the study showed that nitrate concentration ranged from 0.6-3.2 mg/L during October (pre-monsoon) while during January (post-monsoon) the ranged from 1.0 – 3.1 mg/L. Phosphate concentration was ranged from 0.20 – 0.60 mg/L during pre-monsoon and 0.30 – 1.5- mg/L during post-monsoon. The ranged of metalloid such as arsenic was ranged from 5.05 – 32.09 µg/L during pre-monsoon and 5.71 – 22.81 µg/L during post-monsoon. The two highest ranged of heavy metals; copper was from 2.66 – 26.27 µg/L and zinc from 6.02 – 38.61 µg/L for pre-monsoon season while for post-monsoon season the copper ranged from 18.03 – 90.79 µg/L and zinc from 3.42 – 11.34 µg/L. The other values of heavy metals were low compared to these two heavy metals. Results for those parameters level show that Kuantan River can be classified as Class 2 based on INQWS classification which is not heavily polluted. The study revealed that seasonal changes and human activities had affected the quality of water in the river.